2022
DOI: 10.1039/d2cp02819k
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle-induced giant jammed aggregation of active semiflexible filaments

Abstract: Filaments driven by bound motor proteins and chains of self-propelled colloidal particles are typical example active polymers (APs). Due to deformability, APs exhibit very rich dynamic behaviors and collective assembling...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Moreover, a small number of long cells helps to organize the dynamics of the bacterial colony, with long cells acting as nucleation cites around which aggregates of short, rapidly moving cells can form (figures 16(c) and (d)). For homogeneous active polymers, Wang et al [103] found that their assembly is a two-state system in the presence of a big single obstacle (figures 16(e)-(m)), that is, all filaments either disperse freely in space or gather almost completely together into a giant jammed aggregate attached to the surface of the obstacle. In the absence of the obstacle, an active polymer chain is known to bend and form spiral configuration at low rigidity or strong propulsion [81].…”
Section: Nucleation and Growthmentioning
confidence: 99%
“…Moreover, a small number of long cells helps to organize the dynamics of the bacterial colony, with long cells acting as nucleation cites around which aggregates of short, rapidly moving cells can form (figures 16(c) and (d)). For homogeneous active polymers, Wang et al [103] found that their assembly is a two-state system in the presence of a big single obstacle (figures 16(e)-(m)), that is, all filaments either disperse freely in space or gather almost completely together into a giant jammed aggregate attached to the surface of the obstacle. In the absence of the obstacle, an active polymer chain is known to bend and form spiral configuration at low rigidity or strong propulsion [81].…”
Section: Nucleation and Growthmentioning
confidence: 99%
“…This motivates the interdisciplinary research of polymer physics and active matter. [7][8][9][10][11][12][13][14][15][16][17][18][19] Polymeric active matters or active polymers (APs) are not unusual in living systems. Some examples include microtubules/microfilaments driven by motor proteins, 20,21 DNA/RNA molecules in transcription, 22 slender bacteria, 23 algae or bacteria that can organize into a chain-like structure, 24 and macroscopic worms.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, several studies on APs in contact with obstacles have appeared in the literature. 19,[32][33][34] Active semiflexible polymers are found to form a giant jammed aggregate around a circular obstacle. 19 And, in porous media, flexible APs are observed forming spirals and getting stuck, while stiff ones are found moving smoothly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems involving self-propelled particles have aroused great interest in non-equilibrium statistical physics [1][2][3][4][5] in recent years. In practice, the self-propelled particles have been utilized for implementations ranging from cargo and drug delivery [6][7][8] to environmental engineering.…”
Section: Introductionmentioning
confidence: 99%